Social Enterprises in Structurally Weak Rural Regions: Innovative Troubleshooters in Action. Handbook for Practitioners - Jamie Scott Baxter; Georgios Chatzichristos; Gabriela Christmann; Barraí Hennebry; Sunna Kovanen; Marina Novikova; Lucas Olmedo; Sune W. Stoustrup; Mara van Twuijver; Anna Umantseva (Leibniz-Institut für Raumbezogene Sozialforschung (IRS), 2020)
Structurally weak rural regions are faced with major economic and social challenges. In comparison to predominantly urban regions, they are economically less productive. They provide fewer desired goods and services and the labour market offers few career opportunities. Shops where daily purchases can be made are scarce, and it is challenging for the inhabitants to move around the region because public transport is very limited. Against this background, the respective regions have experienced considerable declines in populations and, in particular, a brain drain of the young. Downward spirals have been set in motion that have further reduced the number of economic opportunities.
Keywords: 710